Comparison of Gut Microbiota of Yaks From Different Geographical Regions - Liu, Wenwen; Wang, Qiang; Song, Jiajia; Xin, Jinwei; Zhang, Songshan; Lei, Yuanhua; Yang, Yuanli; Xie, Peng; Suo, Huayi (Frontiers in Microbiology, 2021)
Gut microbiota are closely linked to host health and adaptability to different geographical environments. However, information on the influence of different geographical conditions on the intestinal microbiota of yaks is limited. In this study, 18 yak fecal samples were collected from three regions of China, namely Shangri-la, Lhasa, and Yushu, and were analyzed via high-throughput sequencing. The alpha diversity, as measured by the Shannon, ACE, and Chao indices, was the highest in the Shangri-la samples. Principal coordinate analysis detected significant differences in the composition of the intestinal microbiota of yaks from different regions. A total of 6 phyla, 21 families, and 29 genera were identified in the fecal samples. The dominant phyla in the samples were Firmicutes and Bacteroidetes, and the most abundant family was Ruminococcaceae. In addition, Ruminococcaceae_UCG-005 was the predominant genus and was more abundant in Yushu samples than in other samples. However, the predicted functional gene composition of the gut microbiota of yaks from different regions was similar. Our results revealed that geographical conditions influence the diversity and composition of the intestinal microbiota of yaks.